Laser NIR irradiation enhances antimicrobial photodynamic inactivation of biofilms of Staphylococcus aureus - Mamone, Leandro Ariel (2024)
Photodynamic inactivation (PDI) utilizes a photosensitizer (PS) activated by visible light togenerate reactive oxygen species (ROS), to kill bacteria. PDI is effective against planktonicmicroorganisms, but biofilms are less sensitive due to limited PS and oxygen penetration.Near-infrared treatment (NIRT), involve the use of near-infrared light to kill bacteria either viathermal effects or ROS production.Our objective was to enhance S. aureus biofilm´s sensitivity to PDI by pre-treating with NIRirradiation before visible light exposure.In an in vitro biofilm model, laser NIRT (980 nm) followed by exposure to PDI, showed asynergistic effect on bacterial viability loss (4-log CFU vs 1-log loss with individualtreatments). Interestingly, pre-heating liquid medium had no significant impact on PDIefficacy, suggesting that both thermal and non-thermal effects of NIR may be involved.NIRT increased PS uptake, induced clefts in the biofilm matrix, and released bacterial cellsfrom the biofilm. NIRT induced a transient increase in the temperature to 46°C of in vitrocultures, however under the same conditions, when mice were irradiated, skin temperature roseto 37°. Our findings suggest that NIR irradiation serves as a complementary treatment to PDI,allowing reducing PS concentration, and highlighting its potential as an effective and resource46 efficient antibacterial approach